Storm water: pollutant characterisation and treatment practices - Ekanayake, D.; Loganathan, P.; Kandasamy, J.; Vigneswaran, S. (University of Jaffna, 2022)
Stormwater quantity and quality can vary widely depending on the landscape of the area and amount and intensity of precipitation. Stormwater is a good source of water which can reduce the demand on potable water supply. Treated stormwater can also be employed for non-potable uses which account more than 40% of household domestic water demand. Wetlands, bio-retention, and permeable pavements are widely used in stormwater management. Current bio retention systems used in Australia for stormwater pollution control seldom provide the water quality necessary for water recycling due to their varies removal efficiency for a range of inflow conditions and pollutants. Stormwater discharge in certain periods is relatively large, and therefore, it needs to be treated intensively at high rates. There is a large gap of research data available on improving bio-retention media for effective stormwater treatment.
Keywords: Stormwater; Characterization; Treatment